THE INFLUENCE OF PERSONALITY TRAITS AND EMPLOYEE DEVELOPMENT ON THE JOB PERFORMANCE OF ENGINEERS IN MALAYSIA - Leong Weng Beng, Tony; Muthuveloo, Rajendran (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2020)
Penelitian ini mempelajari bagaimana ciri-ciri kepribadian mempengaruhi kinerja kerja insinyur di Malaysia dan bagaimana pengembangan karyawan memastikan kinerja kerja yang optimal dalam lingkungan yang terus berubah. Sampel insinyur yang bekerja di perusahaan berbasis Elektro dan Elektronika dan hasilnya menunjukkan bahwa Extraversion dan Openness berkorelasi positif dengan Prestasi Kerja sementara Agreeableness dan Neuroticism berkorelasi negatif. Itu juga menunjukkan bahwa pengembangan karyawan memoderasi hubungan antara Kepribadian dan Prestasi Kerja untuk individu dengan tingkat Conscientiousness yang tinggi. Penemuan ini menunjukkan bahwa individu dengan ciri kepribadian yang berbeda mempersepsikan dan menanggapi upaya pengembangan karyawan secara berbeda, dengan demikian pentingnya rencana pengembangan individual.  This paper studies how personality traits affect the job performance of engineers in Malaysia and how employee development ensures optimal job performance in an environment of constant change. A sample of engineers working in Electrical and Electronics based companies were studied and the results showed that Extraversion and Openness were positively correlated to Job Performance while Agreeableness and Neuroticism were negatively correlated. It was also shown that employee development moderates the relationship between Personality and Job Performance for individuals with high levels of Conscientiousness. These findings show that individuals with different personality traits perceive and respond to employee development efforts differently, thus the importance of individualized development plans.